SIEF 2015. Utopias, Realities, Heritages: Ethnographies for the 21st Century. 12th Congress of the Société Internationale d’Ethnologie et de Folklore (SIEF). Zagreb, Croatia, 21–25 June 2015 - Nada Kujundžić (Croatia, 2025)
Report on the SIEF 2015 Congress